Cost-Benefit Analysis of Fruit Tree Based Agro-Forestry Systems: The Case of The Htee Pu Climate-Smart Village, Nyaung-U Township, Central Dry Zone, Myanmar - Manilay, Alessandro A.; Thant, Phyu Sin; Myae, Chan; Barbon, Wilson John; Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2022)
Htee Pu is a farming village located in the Central Dry Zone of Myanmar, where drought, high atmospheric temperature, and infertile and degraded soils are constraints to sustaining and increasing agricultural productivity and farm income. Dryland fruit-tree-based agroforestry and the raising of goats were the prominent CSA options introduced to supplement the risk-prone prevalent annual cropping systems. This study was conducted to measure the financial benefits of introducing dryland-appropriate fruit trees (with one group having an additional complementary goat component) to Htee Pu households. The Cost and Return Analysis, Payback Period for Investment Analysis, and Household Liquidity Analysis were the analytical methods that were used in the study. Estimating the Net Value generated from potential fruit harvests showed that planting fruit trees on farms or homesteads can be highly profitable. Adding the financial benefits from fruit trees to the households’ farm and off-farm income resulted in improvements in the liquidity condition of a number of households. While the Cost-Benefit Analysis results were less impressive than the fruit tree project, the longer-term outcomes would improve once all the female goat breeders had reached their reproductive age. Goats would be significant additional sources of income and food for home consumption, thus a relevant CSA option as well.